Quality and durability properties and life-cycle assessment of high volume biomass fly ash mortar. (10th February 2019) - Teixeira, E.R.; Mateus, R.; Camões, A.; Branco, F.G.
Highlights: Environmental benefits of incorporating coal and biomass fly ashes on concrete. Coal and biomass fly ashes were incorporating on mortar as cement replacement. Biomass fly ash were used as reservoir of alkalinity. Mortars with BFA and CFA have good quality, durability and sustainability. BFA can lead to a minimization of the issues related to the HVFAC. Abstract: The effect of using biomass fly ash (BFA) on the quality, durability and sustainability of mortars was studied. Using high amounts of BFA does not lead to a production of mortars with better performance than a plain cement mortar. However, when BFA is used in small amounts mixed with coal fly ash, mortars with similar compressive strength, to that of a cement mortar, but with less carbonation and with better environmental performance are obtained. Using BFA in the concrete industry can lead to a minimisation of issues related to the high volume fly ash concrete.